Comparing the Effects of the mTOR Inhibitors Azithromycin and Rapamycin on In Vitro Expanded Regulatory T Cells. Issue 12 (December 2019) - Bergström, Marcus; Müller, Malin; Karlsson, Marie; Scholz, Hanne; Vethe, Nils Tore; Korsgren, Olle
Adoptive transfer of autologous polyclonal regulatory T cells (Tregs) is a promising option for reducing graft rejection in allogeneic transplantation. To gain therapeutic levels of Tregs there is a need to expand obtained cells ex vivo, usually in the presence of the mTOR inhibitor Rapamycin due to its ability to suppress proliferation of non-Treg T cells, thus promoting a purer Treg yield. Azithromycin is a bacteriostatic macrolide with mTOR inhibitory activity that has been shown to exert immunomodulatory effects on several types of immune cells. In this study we investigated the effects of Azithromycin, compared with Rapamycin, on Treg phenotype, growth, and function when expanding bulk, naïve, and memory Tregs. Furthermore, the intracellular concentration of Rapamycin in CD4+ T cells as well as in the culture medium was measured for up to 48 h after supplemented. Treg phenotype was assessed by flow cytometry and Treg function was measured as inhibition of responder T-cell expansion in a suppression assay. The concentration of Rapamycin was quantified with liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). Azithromycin and Rapamycin both promoted a FoxP3-positive Treg phenotype in bulk Tregs, while Rapamycin also increased FoxP3 and FoxP3+Helios positivity in naïve and memory Tregs. Furthermore, Rapamycin inhibited the expansion of naïve Tregs, but also increased their suppressive effect. Rapamycin was quickly degraded in 37°C medium, yet was retained intracellularly. While both compounds may benefit expansion of FoxP3+ Tregs in vitro, further studies elucidating the effects of Azithromycin treatment on Tregs are needed to determine its potential use.